2016
DOI: 10.1001/jamadermatol.2016.2668
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Occult Invasion in Melanoma In Situ

Abstract: IMPORTANCE It is unclear why some patients with in situ melanoma develop metastases. Few reports demonstrate occult invasion with immunohistochemistry staining, which were discordant with reports interpreting such staining as false-positive. OBJECTIVE To investigate the occurrence of occult invasive disease within in situ melanoma by using methods to circumvent potential limitations in prior study designs. DESIGN, SETTING, AND PARTICIPANTS Unequivocal in situ melanoma without associated nevi or regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Lastly, the perception that melanocytic markers, such as Melan‐A, can more accurately stage melanomas is a potential explanation for its increased usage over the duration of the study period. For example, several studies have examined the use of Melan‐A in melanoma in situ cases in order to improve detection of invasion . In our study, although overall immunostain usage increased over time, we found that immunostains were actually less likely to be used in the diagnosis of MIS.…”
Section: Discussionmentioning
confidence: 63%
“…Lastly, the perception that melanocytic markers, such as Melan‐A, can more accurately stage melanomas is a potential explanation for its increased usage over the duration of the study period. For example, several studies have examined the use of Melan‐A in melanoma in situ cases in order to improve detection of invasion . In our study, although overall immunostain usage increased over time, we found that immunostains were actually less likely to be used in the diagnosis of MIS.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to diagnostic assurance of melanocytic lineage, other reasons for using IHC stains in suspected melanoma include depth determination in the presence of fibrotic change or regression, and when there is copious pigmentary incontinence of melanin‐laden histiocytes. IHC staining can also be used in the setting of dense inflammation, so as to identify small groups of cells in the dermis that might represent superficial invasion . Interestingly, our data show that melanoma in situ was more likely to have IHC stains utilized than was invasive melanoma.…”
Section: Discussionmentioning
confidence: 78%
“…The pathological examination indicated that these cells often exhibit atypical mitosis (Machado et al, 2016). Patients with advanced cancer often exhibited severe systemic symptoms and high recurrence rate after surgical excision, causing a big challenge for cancer therapy (Bax et al, 2016;Bendella et al, 2016;Frohman et al, 2016). In view of the enormous harm caused by cancer, the development of new antitumor treatments has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%